A Framework to Address Challenges in Communicating the Developmental Origins of Health and Disease - Winett, Liana (Curr Environ Health Rep, 2016)
Findings from the field of Developmental Origins of Health and Disease (DOHaD) suggest that some of the most pressing public health problems facing communities today may begin much earlier than previously understood. In particular, this body of work provides evidence that social, physical, chemical, environmental, and behavioral influences in early life play a significant role in establishing vulnerabilities for chronic disease later in life. Further, because this work points to the importance of adverse environmental exposures that cluster in population groups, it suggests that existing opportunities to intervene at a population level may need to refocus their efforts “upstream” to sufficiently combat the fundamental causes of disease. To translate these findings into improved public health, however, the distance between scientific discovery and population application will need to be bridged by conversations across a breadth of disciplines and social roles. And importantly, those involved will likely begin without a shared vocabulary or conceptual starting point. The purpose of this paper is to support and inform the translation of DOHaD findings from the bench to population-level health promotion and disease prevention, by: 1) Discussing the unique communication challenges inherent to translation of DOHaD for broad audiences, 2) Introducing the First-hit/Second-hit Framework with an epidemiologic planning matrix as a model for conceptualizing and structuring communication around DOHaD, and 3) Discussing the ways in which patterns of communicating DOHaD findings can expand the range of solutions considered, and encourage discussion of population-level solutions in relation to one another, rather than in isolation.